Global prevalence of, and risk factors for, uninvestigated dyspepsia: a meta-analysis - Ford, Alexander C; Marwaha, Avantika; Sood, Ruchit; Moayyedi, Paul (Gut, 2015)
ObjectivesMany cross-sectional surveys have reported the prevalence of uninvestigated dyspepsia, but there has been no recent systematic review of data from all studies to determine its global prevalence and risk factors.DesignMEDLINE, EMBASE and EMBASE Classic were searched (until January 2014) to identify population-based studies that reported the prevalence of uninvestigated dyspepsia in adults (≥15 years old); dyspepsia was defined using symptom-based criteria or questionnaires. The prevalence of dyspepsia was extracted for all studies and according to the criteria used to define it. Pooled prevalence, according to study location and certain other characteristics, ORs and 95% CIs were calculated.ResultsOf the 306 citations evaluated, 103 reported the prevalence of uninvestigated dyspepsia in 100 separate study populations, containing 312 415 subjects. Overall pooled prevalence in all studies was 20.8% (95% CI 17.8% to 23.9%). The prevalence varied according to country (from 1.8% to 57.0%) and criteria used to define dyspepsia. The greatest prevalence values were found when a broad definition of dyspepsia (29.5%; 95% CI 25.3% to 33.8%) or upper abdominal or epigastric pain or discomfort (20.4%; 95% CI 16.3% to 24.8%) were used. The prevalence was higher in women (OR 1.24; 95% CI 1.13 to 1.36), smokers (OR 1.25; 95% CI 1.12 to 1.40), non-steroidal anti-inflammatory drug (NSAID) users (OR 1.59; 95% CI 1.27 to 1.99) and Helicobacter pylori-positive individuals (OR 1.18; 95% CI 1.04 to 1.33).ConclusionsThe overall pooled prevalence of uninvestigated dyspepsia was 21%, but varied among countries and according to the criteria used to define its presence. Prevalence is significantly higher in women, smokers, NSAID users and H. pylori-positive individuals, although these associations were modest.